Early Interventions to Prevent Posttraumatic Stress Disorder Symptoms in Survivors of Life-Threatening Medical Events: A Systematic Review - Birk, Jeffrey L. (J Anxiety Disord, 2019)
Post-traumatic stress disorder (PTSD) induced by life-threatening medical events has been associated with adverse physical and mental health outcomes, but it is unclear whether early interventions to prevent the onset of PTSD after these events are efficacious. We conducted a systematic review to address this need. We searched six biomedical electronic databases from database inception to October 2018. Eligible studies used randomized designs, evaluated interventions initiated within 3 months of potentially traumatic medical events, included adult participants, and did not have high risk of bias. The 21 included studies (N = 4,486) assessed a heterogeneous set of interventions after critical illness (9), cancer diagnosis (8), heart disease (2), and cardiopulmonary surgery (2). Fourteen psychological, 2 pharmacological, and 5 other-type interventions were assessed. Four of the psychological interventions emphasizing cognitive behavioral therapy or meaning-making, 1 other-type palliative care intervention, and 1 pharmacological-only intervention (hydrocortisone administration) were efficacious at reducing PTSD symptoms relative to control. One early, in-hospital counseling intervention was less efficacious at lowering PTSD symptoms than an active control. Clinical and methodological heterogeneity prevented quantitative pooling of data. While several promising interventions were identified, strong evidence of efficacy for any specific early PTSD intervention after medical events is currently lacking.